Analysis of the methods of determining wear of parts - Demchenko, M. (Запоріжжя : ТДАТУ, 2024)
EN: Special methods are used to study the wear resistance of machine parts. The main requirements for wear determination methods are the minimum time for the wear determination test; undesirability of frequent disassembly and reassembly of nodes; the parts during the test should not wear much. The methods can be divided into 2 groups: 1) Production, which include the micrometering method, the method of indirect assessment of changes in the operational characteristics of the joints of parts; 2) Laboratory: weighing of parts, determination of wear products in lubricants, method of radioactive isotopes, method of artificial bases, profiling. The micrometric measurement method is based on determining the linear dimensions of parts that were in use by measuring with universal means (micrometers, calipers, indicators, etc.) before and after wear. Advantages of the method: direct measurement, simplicity, availability, possibility of observing wear surfaces. Disadvantages: the length of the tests and high labor intensity, the dependence of the results on the deformation of the part, the inevitability of assembly and disassembly.
Keywords: wear of parts; machine; profilography method